ACTION RESEARCH FOR THE IMPROVEMENT OF MOBILE AND SOCIAL MEDIA JOURNALISM STUDIES - Veronika Veronika; Fathia Barnez; Fitri Murfianti (ASPIRATION Journal, 2021)
Mobile phone and social media are very inherent in human life today. These device and platform then becomes a tool to help or facilitate human life, including working activities. One of them is in the field of journalism. This is replicated in the journalism curriculum at universities. This study uses action research method to evaluate mobile and social media journalism class at Universitas Multimedia Nusantara.This study aims to know the level of understanding and ability of students related to mobile and social media journalism and the final result or evaluation of the course. This research uses survey and in-depth interview for collecting the data. 87 students took a part in this study; then the result was explored by conducting in-depth interviews with unique samples of student. The result, students who have taken the mobile and social media journalism course already have the knowledge and ability to use mobile devices and social media platform. The challenge is when they uses a mobile device in the news production process and in the news editing process because of the characteristics of the device (small screen). Knowledge of the specifications of each editing application is very helpful as a mobile journalist. The class will be more ideal with learning how to reporting or hosting news which is very common on social media platform.